SERTIFIKASI GURU Telaah Urgensinya Terhadap Kompetensi Dan Profesionalisme Guru Agama - Fachrudddin Fachrudddin (State Islamic University North Sumatra, 2009)
Abstract: Teacher Certification: Analysis of its Importance for the Competency and Professionalism of Religious Teacher. Indonesian national policy on human resource development is now focusing on education— a trend taken after the Reformation Era. The administration is trying to achieve this through enhancing teachers’ professionalism and prosperity. One main means of this is teachers’ certification that is designed to: 1) determine the qualification level of teachers as learning agent; 2) increase the process and education results; 3) increase teachers’ social status; 4) increase teachers’ professionalism; and 5) increase teachers’ prosperity. Amidst the efforts and hopes one has to wait for the results.Kata Kunci: sertifikasi guru, kompetensi, profesionalisme